2019
DOI: 10.5114/aoms.2019.89704
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of microRNA-125b enhances the expression of STAT3 and contributes to cholesteatoma growth

Abstract: Introduction: MicroRNA-125b has been found to be down-regulated in many types of malignant tumours and diseases with excessive proliferation of keratinocytes, such as cutaneous squamous cell carcinoma and psoriasis. Cholesteatoma, which is mainly composed of keratinocytes, also has characteristics of abnormal proliferation similar to a malignant tumour. However, the expression and regulatory mechanisms of miR-125b and its downstream genes in cholesteatoma have not been clarified. Material and methods: Real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Zang et al [44] observed downregulation of miR-125b and upregulation of STAT3, cyclin D1, survivin, and VEGF in cholesteatoma tissues, which is consistent with the results of previous studies [17,57,102,103]. These reports imply that the inhibition of miR-125b expression in cholesteatoma may contribute to high proliferation and low apoptosis through an increased expression of STAT3, which could be used as a potential therapeutic target for intratympanic pharmacotherapy of cholesteatoma [17].…”
Section: Microrna-125 and Circ_0074491supporting
confidence: 84%
See 3 more Smart Citations
“…Zang et al [44] observed downregulation of miR-125b and upregulation of STAT3, cyclin D1, survivin, and VEGF in cholesteatoma tissues, which is consistent with the results of previous studies [17,57,102,103]. These reports imply that the inhibition of miR-125b expression in cholesteatoma may contribute to high proliferation and low apoptosis through an increased expression of STAT3, which could be used as a potential therapeutic target for intratympanic pharmacotherapy of cholesteatoma [17].…”
Section: Microrna-125 and Circ_0074491supporting
confidence: 84%
“…In total, 118 articles were retrieved through the database search. After applying the search strategy described above, a total of 18 articles were identified that met all inclusion criteria [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A flow diagram of the detailed study selection process is presented in Figure 1.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations